Measurement of gluconeogenesis in exercising men by mass isotopomer distribution analysis - Trimmer, Jeff K; Schwarz, Jean-Marc; Casazza, Gretchen A; Horning, Michael A; Rodriguez, Nestor; Brooks, George A (Journal of applied physiology (1985), 2002)
Departments of 1  Integrative Biology and 2  Nutritional Sciences, University of California, Berkeley, California 94720 We evaluated the hypothesis that coordinated adjustments in absolute rates of gluconeogenesis (GNG ab ) and hepatic glycogenolysis (Gly) would maintain euglycemia and match glucose production (GP) to peripheral utilization during rest and exercise. Specifically, we evaluated the extent to which gradations in exercise power output would affect the contribution of GNG ab to GP. For these purposes, we employed mass isotopomer distribution analysis (MIDA) and isotope-dilution techniques on eight postabsorptive (PA) endurance-trained men during 90 min of leg cycle ergometry at 45 and 65% peak O 2 consumption ( O 2 peak ; moderate and hard intensities, respectively) and the preceding rest period. GP was constant in resting subjects, whereas the fraction from GNG (f GNG ) increased over time during rest (22.3 ± 0.9% at 11.25 h PA vs. 25.6 ± 0.9% at 12.0 h PA, P  < 0.05). In the transition from rest to exercise, GP increased in an intensity-dependent manner (rest, 2.0 ± 0.1; 45%, 4.0 ± 0.4; 65%, 5.84 ± 0.64 mg · kg 1 · min 1 , P  < 0.05), although glucose rate of disappearance exceeded rate of appearance during the last 30 min of exercise at 65% O 2 peak . Compared with rest, increases in GP were sustained by 92 and 135% increments in GNG ab during moderate- and hard-intensity exercises, respectively. Correspondingly, Gly (calculated as the difference between GP and MIDA-measured GNG ab ) increased 100 and 203% over rest during the two exercise intensities. During moderate-intensity exercise, f GNG was the same as at rest; however, during the harder exercise f GNG decreased significantly to account for only 21% of GP. The highest sustained GNG ab observed in these trials on PA men was 1.24 ± 0.3 mg · kg 1 · min 1 . We conclude that, after an overnight fast, 1 ) absolute GNG rates increased with intensity of effort despite a reduced f GNG at 65% O 2 peak , 2 ) during exercise Gly is more responsible than GNG ab for maintaining GP, and 3 ) in 12-h fasted men, neither increased Gly or GNG ab nor was their combination able to maintain euglycemia during prolonged hard (65% O 2 peak ) exercise. glycogenolysis; glucose kinetics; glycerol; exertion; glucose production